Quais os benefícios para o município de Santa Maria-RS resultantes dos ingressos de recursos de outros custeios de capital (OCC) pelas unidades do Exército Brasileiro sediadas no município? - Souza, Tomé de (2020)
One of the important sources of revenue for a municipality is the resources coming from other federal entities, for example those that are allocated through the federal public budget. These resources may come from public policies, compensation for tax revenues generation, payment of public servants' remuneration, or, still, expenses related to the public agencies creation or maintenance in a given location, for instance the expenses necessary to maintain the vegetative life of a specific organ, which is the case of resources from other costs and capital (OCC). Considering the city of Santa Maria-RS, which has one of the largest universities in the country, the second largest military contingent in Brazil, in addition to several other federal agencies, these resources are strategic for the municipality's economy. Furthermore, the city has a low level of industrialization, that makes this type of resource more crucial. In this case study, all commitment notes issued by all Brazilian Army Management Units (UG) and Military Organizations (OM) based in the municipality were verified, in order to analyze the destination of these resources and their impacts in Santa Maria, as well as measuring the losses caused by her evasion. It was observed that, of all the resources that directed to Santa Maria in the studied period, through the military organizations of the Brazilian Army, as OCC, about a quarter of them remained in companies in the municipality, which represented 0.214% of the municipality's GDP. Meanwhile, about three quarters of these resources were committed and spent in other municipalities, which represented an evasion of about 0.552% of the municipality's GDP. The same occurred in relation to the possibility of creating jobs in the municipality. Considering this, even though there is a tenfold risk of incurring canceled leftovers registration, therefore, resources to be lost, in companies outside the municipality. The loss of direct collection, through services tax, did not represent an incredibly significant percentage, since the municipality collected about three quarters of this type of tax.